Student Perspectives on Talking About Sexual Assault in Australian Law Classes - Anna Belgiorno-Nettis (Legal Education Review)
Dwindling student attendance and engagement in lectures is a significant concern for higher education providers. An increasing reliance on online recordings as a substitute for face-to-face teaching, coupled with students taking on a wider range of commitments, has led to lower attendance rates, particularly in lectures. This article explores how transformative teaching, which utilises engaging and interactive methods of teaching to challenge, redefine, and ‘transform’ students’ learning and critical thinking, can be used to adapt lectures in order to maximise student engagement and learning. Empirical data collected from students, academic staff, and executive members at the University of Western Australia Law School are used to display a strong willingness to alter, but not radically depart from, the traditional ‘information transfer’ lecture. This is particularly important in catering for a generation of students with unprecedented connectivity, technological grasp, and a thirst for constant engagement. The results suggest that the best path to ‘transform’ law lectures is implementing scaffolded problem-based exercises, increasing student input into learning processes and decision-making, and ensuring buy-in and recognition of workloads across all student, staff, and executive levels. This will maximise student attendance, enjoyment, and engagement at lectures while ensuring that academic staff do not bear a disproportionate burden in creating change.